THE PROBLEM OF DISTRIBUTION OF INHERITANCE: A CASE STUDY ON THE MALAY COMMUNITY OF SAMBAS KALIMANTAN BARAT IN INDONESIA - Asman, Asman (Jurnal Syariah, 2020)
This study is about the provisions of the Qur’ān on inheritance that regulates the rights of the heirs with justice, especially towards women who did not have such right before the advent of Islam. Currently, the people of Malay Sambas distribute inheritance against the provisions of the Qur’ān which allots double shares to the male except in case of the parents. In the Sambas Malay community, men and women inherit equal shares contrary to the provisions in the Qur’ān as stated in the verse of al-Nisā’ 4: 11, 12, and 176. This research is a field research with a phenomenological method by looking at gender equality and feminism in the distribution of inheritance among the Malay Sambas community. The focus of this research is guided by the Islamic law position on the Malay Sambas equal distribution system of inheritance between men and women. This research finds that the Malay Sambas system of inheritance is contrary to the Shariah because there is still equal distribution of inheritance to male and female beneficiaries.